LEXICAL AMBIGUITY IN THE HEADLINES OF THE JAKARTA POST NEWSPAPER - Nanda Ramadani (English Department, Faculty of Humanities, Andalas University, 2015)
The purposes of this research are to find the ambiguous words that have many lexical meanings from the headline of The Jakarta Post newspaper, and to classify the forms of the ambiguous words. The lexical ambiguity is divided into two forms Ullmann (1962): polysemy and homonymy. Another semantics’ theories used in this research are from Lyons (1995), Palmer (1981), and Leech (1981). In this research, the writer takes 10 data from 9 headlines of the newspaper that contain lexical ambiguity. In collecting the data, the writer uses note taking technique and non-participant observational technique. The writer took the data from the website of The Jakarta Post, then collected them in the note in order to make it easier in the analysis. In analyzing the data, the writer uses the semantic theories and Oxford Advanced Learners dictionary to find the lexical meanings of the ambiguous words. After that, the writer classifies the form of lexical ambiguity, whether it is polysemy or homonymy. In presenting the result of analysis, the writer uses formal and informal methods. The writer finds that all of the data, 10 ambiguous words from 9 headlines are categorized into the polysemy.Key words: ambiguity, polysemy, homonymy